Management of asymptomatic arrhythmias: a European Heart Rhythm Association (EHRA) consensus document, endorsed by the Heart Failure Association (HFA), Heart Rhythm Society (HRS), Asia Pacific Heart Rhythm Society (APHRS), Cardiac Arrhythmia Society of Southern Africa (CASSA), and Latin America Heart Rhythm Society (LAHRS). Issue 6 (18th March 2019) - Arnar, David O; Mairesse, Georges H; Boriani, Giuseppe; Calkins, Hugh; Chin, Ashley; Coats, Andrew; Deharo, Jean-Claude; Svendsen, Jesper Hastrup; Heidbüchel, Hein; Isa, Rodrigo; Kalman, Jonathan M; Lane, Deirdre A; et al.
Abstract: Asymptomatic arrhythmias are frequently encountered in clinical practice. Although studies specifically dedicated to these asymptomatic arrhythmias are lacking, many arrhythmias still require proper diagnostic and prognostic evaluation and treatment to avoid severe consequences, such as stroke or systemic emboli, heart failure, or sudden cardiac death. The present document reviews the evidence, where available, and attempts to reach a consensus, where evidence is insufficient or conflicting.